2023
DOI: 10.1109/jstars.2023.3247455
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Inspired Remote Sensing Interpretation: A Comprehensive Survey

Abstract: Brain-inspired algorithms have become a new trend in next-generation artificial intelligence. Through research on brain science, the intelligence of remote sensing algorithms can be effectively improved. This paper summarizes and analyzes the essential properties of brain cognise learning and the recent advance of remote sensing interpretation. Firstly, this paper introduces the structural composition and the properties of the brain. Then, five represent brain-inspired algorithms are studied, including multisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 317 publications
0
8
0
Order By: Relevance
“…There are restrictions on the kinds of scenes that can be reconstructed using these methods, as they are designed to only use a single input view at test time [ 82 ]. Results from single-view 3D reconstruction are typically incomplete and inaccurate, particularly in cases where there are obstructions or obscured regions [ 114 ].…”
Section: Object Reconstructionmentioning
confidence: 99%
“…There are restrictions on the kinds of scenes that can be reconstructed using these methods, as they are designed to only use a single input view at test time [ 82 ]. Results from single-view 3D reconstruction are typically incomplete and inaccurate, particularly in cases where there are obstructions or obscured regions [ 114 ].…”
Section: Object Reconstructionmentioning
confidence: 99%
“…A survey conducted on brain-inspired algorithms employed on remote sensing data interpretation revealed that through interaction with the environment, reinforcement learning in remote sensing chooses consecutive actions by maximizing cumulative feature rewards. Reinforcement learning can achieve relatively high accuracy without utilizing any labelled training dataset, especially when there are only a few labelled pixels available [27]. The classification of polarimetric synthetic aperture radar images was proposed using an improved deep Q-network algorithm for few-shot remote sensing data.…”
Section: B Reinforcement Learningmentioning
confidence: 99%
“…Remote sensing foundation models [30] have received widespread attention in the last three years. Researchers have made many breakthroughs, achieving effective learning on various modalities and tasks.…”
Section: Foundation Models In Remote Sensingmentioning
confidence: 99%